PENERAPAN KNOWLEDGE MANAGEMENT SYSTEM PADA DINAS SOSIAL PROVINSI SULAWESI SELATAN - Andi Muhammad Idzhar (Jurnal Administrasi Negara, 2021)
This research aims to analyze the implementation of knowledge management in the social service of south Sulawesi province, which seen from three basic processes or stages of implementing knowledge management in organization, i.e. knowledge creation, knowledge sharing, and knowledge implementation. The research method used in this research was qualitative descriptive, that is qualitative research will describe how the basic process or stages of implementing knowledge management in government agencies. The data collection methods used were interviews, observation, and review documents. This research involved 13 informants who were selected based on the considerations of the most parties that involved by considering strategic position and tenure in the social service, especially regarding the implementation of knowledge management. The results indicated that the implementation of knowledge management in process or stages of knowledge creation in the social service of south Sulawesi province was not fully implemented. The activities that have been implemented and done regularly, that is informal meetings and learning by doing. Likewise, the knowledge sharing stage has not been fully implemented in the social service of south Sulawesi province, only the activity of using interactive media has been going well. And last, almost all of the knowledge implementation in the social service of south Sulawesi province has not been implemented, although there are several activities have been done on these stages. However, researcher assume that has not been done in particular and optimally, such as infrastructure assessment activities in form of data collection on equipment needs and giving reward system.